Comparação de métodos usados para estimar coeficientes de digestibilidade de uma ração comercial felina para jaguatiricas (Leopardus pardalis) - Carvalho, Anderson Luiz de (2010)
An experiment was realized to compare different methods to determine nutrient digestibility of a dry kibble diet for ocelots (Leopardus pardalis). Total collection (TC) and internal markers were used to study the digestibility of dry matter (DM), crude protein (CP), ether extract (EE), nitrogen-free extract (NFE) and gross energy (GE) of a commercial feline diet with 30.8 % of CP and 23.8% of EE. Acid insoluble ash (AIA), crude fiber (CF) and acid detergent fiber (ADF) were the marker methods used to estimate the apparent digestibility of DM, CP, EE, NFE and GE. Six adult animals, male (n=4) and females (n=2), with average weight of 12.45 ± 1.37 Kg, received the diet during 10 days prior to the total collection period. The AIA method showed no difference from TC (P>0.05) and can be used to determine digestibility coefficients for ocelots. The CF and ADF markers underestimated the digestibility obtained by total collection method and are not recommended to estimate these coefficients in ocelots (P<0.05). It is concluded that the CIA indicator can be used as an alternative to determine the digestibility of dry kibble diets for ocelots